Interactive effect of water and nitrogen fertilization improve chlorophyll fluorescence and yield of maize. (13th December 2022) - Gao, Fei; Wang, Gui Yang; Muhammad, Ihsan; Tung, Shahbaz Atta; Zhou, Xun Bo
Abstract: Water scarcity and excessive N fertilization have a negative effect on maize ( Zea mays L.) production. Low water and N fertilization are the major problem in sustainable agriculture by limiting crop growth and development. However, the combined effect of N fertilization and supplementary irrigation on chlorophyll fluorescence and maize yield is still not understood. The objective of the study was to signify the effect of supplementary irrigation and N fertilization on leaf area index (LAI), relative chlorophyll content (SPAD), maximum photosynthetic capacity ( Fv / Fm ), photochemical quenching coefficient (qP), and yield. The experiment was conducted in a split‐plot design, with water management in main plot and N fertilization in subplot with three replications. Treatments included two water managements, that is, rainfed (natural rainfall) and irrigation water (70% field capacity). Five N fertilization rates were N0 (0 kg N ha −1 ), N150 (150 kg N ha −1 ), N200 (200 kg N ha −1 ), N250 (250 kg ha −1 ), and N300 (300 kg N ha −1 ). The LAI, SPAD, Fv / Fm, qP, and yield were significantly affected by water management, N rates, and their interaction ( P < .05). The LAI, SPAD, Fv / Fm, qP, total dry matter accumulation, and yield under supplementary irrigation were significantly increased by 10.99, 5.75, 6.57, 9.14, 15.64, and 14.58% than those under rainfed conditions, but the nonphotochemical quenching coefficient was significantly decreased by 22.82%. The 250 kg N ha −1 increased grain yield under irrigated conditions than that of other N treatments. The interaction between water management and N fertilization significantly and positively affected the SPAD, Fv / Fm, and grain yield in both years, but had no significant effect on LAI during 2021 and HI during 2020 and 2021. We concluded that N250 treatment with supplementary irrigation increased grain yield. Core Ideas: The effect of supplementary irrigation and N fertilization were studied on chlorophyll fluorescence. Compared with rainfed, photosynthetic capacity and photochemical quenching were higher with supplementary irrigation. Leaf area index and maximum photosynthetic capacity were higher at silking stage than other growth stages. Nonphotochemical quenching coefficient was lower with 300 kg N ha −1 at silking stage than other N rates.